ChemInform Abstract: Electronic Structure, Chemical Bonding and Electrochemical Characterization of Li2CuSn2 and Li2AgSn2. Issue 3 (January 2015) - Schirmer, Niels; Winter, Florian; Matar, Samir F.; Balducci, Andrea; Poettgen, Rainer
Abstract The title compounds are characterized by DFT electronic structure calculations and electrochemical measurements.